2017
DOI: 10.1590/2317-1545v39n2159173
|View full text |Cite
|
Sign up to set email alerts
|

Quality of organically produced bell pepper seeds

Abstract: -The production of bell pepper seeds may be affected by the plant management and harvesting point of fruits. The goal of this study was to evaluate the quality of organically produced bell pepper seeds according to free plant growth, branch thinning and ripening stage. The experiment was conducted in a greenhouse with randomized block design; plants were tutored to parallel tape supports, with and without branch thinning, and fruits were harvested at three ripening stages (completely green, green/reddish and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Notably, the conservation of papaya at room temperature is desirable, since almost all the fruit marketed at the retail level in Brazil is non-refrigerated. In a similar way, other studies revealed that the production in the organic system is viable and postharvest rest of the fruits improves the physiological potential of the seeds in Capsicum baccatum L. (Pereira et al, 2014) and Capsicum annum L. (Nogueira et al, 2017). The papaya cannot be matured properly if harvested at the immature stage.…”
Section: Fruit Maturationmentioning
confidence: 68%
“…Notably, the conservation of papaya at room temperature is desirable, since almost all the fruit marketed at the retail level in Brazil is non-refrigerated. In a similar way, other studies revealed that the production in the organic system is viable and postharvest rest of the fruits improves the physiological potential of the seeds in Capsicum baccatum L. (Pereira et al, 2014) and Capsicum annum L. (Nogueira et al, 2017). The papaya cannot be matured properly if harvested at the immature stage.…”
Section: Fruit Maturationmentioning
confidence: 68%
“…Brazilian Archives of Biology and Technology. Vol.64: e21200733, 2021 www.scielo.br/babt Nogueira and coauthors [23], evaluating the water content in 'Magda' sweet pepper seeds, found minimum water content of 54% at 70 DAA. Besides that, Vidigal and coauthors [24] also achieved a reduction in water content in yellow sweet pepper, with a minimum of 47% at 75 DAA, without fruit rest.…”
Section: Resultsmentioning
confidence: 99%
“…Pepper (Capsicum annuum L.) seeds keep seed moisture at maturity [2], and high germination percentage is not simply attained because of the subsequent flowering on the mother plant. Consequently, the proper harvest time for fruit maturation influences the pepper seeds' seed quality [3][4][5], which affects high-quality transplant production in pepper. Moreover, immature pepper seeds need a longer time to germinate and lose quality faster.…”
Section: Introductionmentioning
confidence: 99%